2013
DOI: 10.1007/s00276-013-1233-y
|View full text |Cite
|
Sign up to set email alerts
|

CT analysis of C2 pedicles morphology and considerations of useful parameters for screwing

Abstract: These morphological data come from a large series give some help for the C2 pedicle screwing preoperative planning. These lean on 3D measures but also on accessible mark during the procedure and despite the difference of the patient orientation. A CT preoperative planning of the pedicle screwing remains essential because more than 7 % of the pedicles have a diameter lower than 4 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Outer pedicle width dimensions of C2 in this study (average, range of 5.2 ± 0.5 mm) were similar in both as in females to those in Asian [13] and European [17] studies who reported an average range of 5.2 to 5.4 mm and 5.18 ± 1.25 mm respectively. It showed also that PTW was smaller-sized compared to the result of Jay U et al [16], Tomasino et al [18] and Sakamoto et al [19] with an average range of range 6.4-9 mm, 5.6 ± 1.2 mm and 5.5 -7.7 mm respectively.…”
Section: Resultssupporting
confidence: 78%
“…Outer pedicle width dimensions of C2 in this study (average, range of 5.2 ± 0.5 mm) were similar in both as in females to those in Asian [13] and European [17] studies who reported an average range of 5.2 to 5.4 mm and 5.18 ± 1.25 mm respectively. It showed also that PTW was smaller-sized compared to the result of Jay U et al [16], Tomasino et al [18] and Sakamoto et al [19] with an average range of range 6.4-9 mm, 5.6 ± 1.2 mm and 5.5 -7.7 mm respectively.…”
Section: Resultssupporting
confidence: 78%
“…Analysis of the C2 lamina found there was enough space (width and length) to insert a laminar screw. 7,8 We report the reduction of a displaced hangman's fracture by compression across crossed laminar screws. In addition, we were able to reduce the fracture gap by using the clenching reduction technique with a unilateral pedicle screw and an opposite-site laminar screw.…”
Section: Discussionmentioning
confidence: 99%
“…We use this function of OsiriX™ (version 5.5.2, Pixmeo, Geneva, Switzerland) to determine the anatomical variations (i.e., C2 pedicle/VA route) of this region in only two simple steps and additionally to calculate the position, length and angle of screws, as others have described. [ 4 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 2 3 ] However, quite often, it is difficult, and sometimes misleading, to evaluate anatomical bony variations (i.e., C2 pars or pedicle morphology) and vascular anomalies [i.e., high riding vertebral artery (VA)] using only the conventional three orthogonal planes of CT (axial, coronal, and sagittal). [ 4 ] For example, in Figure 1 (a type II odontoid fracture in a 92-year-old patient [case 2]), only by changing the gantry angle of the axial plane (from the plane of the inter-vertebral disc to the possible pedicle angle) is enough to clarify the position of VA. Additionally, frequently the “true” plane is biased either because of suboptimal acquisition technique, or because of patient-related factors, such as scoliosis, rotation, or dislocation of vertebral bodies.…”
Section: Introductionmentioning
confidence: 99%